Role of sleep and stress in metabolic syndrome: a community based cross sectional study in Rishikesh, Uttarakhand - Dakshinamurthy, Senkadhirdasan; Saxena, Vartika; Kumari, Ranjeeta; Mirza, Anissa Atif; Dhar, Minakshi; Mishra, Ashutosh (International Journal Of Community Medicine And Public Health, 2020)
Background: Sleep disturbances and stress may intervene with the physiological processes in human body and act as a modulator of metabolic homeostasis. The aim and objectives of the study were to estimate the person’s average sleep propensity; to estimate the stress level in the study subjects; and to determine the association of sleep and stress with metabolic syndrome. Methods: A community based cross sectional study was conducted in an urban area of Rishikesh. Sample size was calculated to be 478. Data was entered and analyzed using SPSS Version 20.0. Chi-square test was used to examine the association between categorical variables. A p value of <0.05 was considered significant. Results: It was observed that different levels of stress did not have any significant association with metabolic syndrome (MetS) though the odds among individuals with moderate stress were 1.1 times (95% CI 0.6-2.2) higher than those with low stress. The overall sleepiness grading was not significantly associated with Metabolic Syndrome. However, people with mild excessive daytime sleepiness have 4.7 times (95% CI 1.2-18) higher odds of MetS as compared to those with low normal daytime sleepiness. Those with moderate excessive day sleepiness had 1.59 times (95% CI 0.3-8) higher odds of MetS, however it was not statistically significant. Conclusions: Mild excessive daytime sleepiness was associated with an increased risk of metabolic syndrome. People with perceived stress are having higher chance of getting MetS.